Uncertainty propagation in vibrational characteristics of functionally graded carbon nanotube-reinforced composite shell panels. (December 2018) - Pouresmaeeli, S.; Fazelzadeh, S.A.; Ghavanloo, E.; Marzocca, P.
Highlights: Analysis of uncertain vibration of doubly-curved panel via interval analysis method. Assessment of design parameters for uncertainty propagation through nanocomposites. Sensitivity analysis conducted to identify dominant uncertain variables. Study of uncertainty propagation percent in vibration of nanocomposites panels. Abstract: Understanding the effect of mechanical uncertainties can play a significant role in design of the nanocomposites. The uncertain natural frequencies of moderately thick doubly-curved functionally graded composite panels reinforced by carbon nanotube (CNT) are investigated. Specifically, doubly-curved shell panels, including spherical, cylindrical and hyperbolic paraboloid panels are examined. To evaluate uncertainty propagation, uncertainty resources including distribution of the CNT through the thickness as well as the mechanical properties of the CNT and polymer matrix are taken into consideration. To assess the propagated uncertainties in the vibrational characteristics of nanocomposite panels, the interval analysis method is employed while the mechanical properties of nanocomposite panels are predicted using the modified rule of mixture method. Based on the comparison between the results of the present study and those reported in the literature, the accuracy of the results is validated. The sensitivity analysis is performed to distinguish the most prominent uncertain variables. Furthermore, numerical results reveal the influences of various uncertainty resources on the upper and lower bounds of uncertain frequencies and uncertainty propagation percent. Graphical abstract: Variations of normalized sensitivity indices for various spherical functionally graded carbon nanotube-reinforced composites (FG-CNTRC) panels. FG-CNTRCs are denominated as FG-A, FG-V, FG-O and FG-X. In the case of FG-A, the bottom surface of CNTRC panel is CNT-rich, while the top surface of FG-V is CNT-rich. Furthermore, in FG-X case, the bottom and top surfaces of CNTRC panel are CNT-rich, in contrast to FG-O type. Uniformly distribution of CNTs in the CNTRC is labeled as UD.Image, graphical abstract